Does Digitalization Increase Economic Growth? Evidence from ASEAN8 Countries - Raeskyesa, Dewa Gede Sidan; Lukas, Erica Novianti (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2019)
Digitalization has become relevant nowadays, not only because of the exposure of new technologies but also the consideration of its impact on the economy. In that regard, this study aims to analyze the effect of digitalization on economic growth. This study uses a descriptive analysis of the eight ASEAN middle-income countries from 1999 to 2014 as well as panel regression analysis with the dependent variable of GDP per capita growth and independent variables of physical capital, human capital, and ICT indicators. As a result, ICT indicators have a significant positive impact on economic growth, along with physical and human capital. The usage and intensity of ICT have a higher impact than access to ICT. Furthermore, human capital contributes the most among the other variables. We recommend the countries invest more in human capital to utilize ICT because it is the quality of human capital that matters to navigate the era of the digital economy.